The Book-Shop of M. Šlapelienė in Vilnius: Establishment, Organization and Working Order - Vaičiūnaitė, Aušra (Knygotyra, 1993)
The most famous Vilnius book-shop of the beginning of the 20th century was established on the 18th of January 1906. The official owner of the book-shop was M. Šlapelienė. She worked without break during all the time of the book-shop’s existing. The real manager was J. Šlapelis, who managed the commerce of the book-shop. The third owner E. Brazaitytė worked in the book-shop till 1907. The book-shop of M. Šlapelienė was acting without break during 39 years. It was rare case in history of lithuanian book-shops. Wars, national oppression realized by occupation power made the work of the book-shop very difficult. The most harmful were searches that were done by polish occupation power. The book-shop of M. Šlapelienė was of great cultural importance. During the war (1914) it provided with books and manuals new-established Lithuanian schools. Lithuanian libraries, acting in Lithuania and abroad, received books from this book-shop. The book-shop also had commercial lent library. The work of the book-shop was stopped in 1944, when Soviet government prohibited to hold private commercial institutions.